The Influence of Integrated Causalytic Learning Model of Local Wisdom on Mastery of Concepts and Environmental Literacy on Global Warming Material of Grade X Students - Nisa Chaerul Ummah; Joni Rokhmat; Ni Nyoman Sri Putu Verawati; Muhammad Zuhdi (International Journal of Contextual Science Education, 2025)
The physics learning process is generally teacher-centered and provides less opportunity for students to think openly. This learning results in low mastery of concepts and environmental literacy of students. This study aims: (1) to examine the effect of causalytic learning model the integrated with local wisdom on the mastery of concepts on global warming material students class X, (2 to examine the effect of causalytic learning model the integrated with local wisdom on the environmental literacy on global warming material students class X,  (3) to examine the effect of causalytic learning model the integrated with local wisdom on the mastery of concepts and environmental literacy on global warming material students class X. This study is a quantitative study with a quasi-experimental research type. The research design used is a pretest-posttest control group design. The population in this study were all class X students at SMAN 1 Lembar in the 2024/2025 academic year, totaling 229 students and divided into 7 classes. The sampling technique used random sampling so that class X-1 students were selected as the experimental class with a total of 28 students who were given treatment in the form of a causal learning model integrated with local wisdom and class X-3 students as the control class with a total of 27 students who were given treatment in the form of conventional learning. The data collection tool consisted of a concept mastery test in the form of descriptive questions and an environmental literacy questionnaire by considering the results of the validity, reliability, difficulty level, and discriminatory power tests, so that six descriptive questions and 20 questionnaire statement items were obtained. Before the hypothesis test was carried out, a hypothesis prerequisite test was first carried out, namely the normality test and the homogeneity test. Based on the data analysis, the average value of the final concept mastery test results in the experimental class (81.11) with the criteria "Good" and the control class (76.93) with the criteria "Good". The results of the environmental literacy data analysis showed that the average value of students in the experimental class (82.11) with the criteria "Good" and the control class (76.11) with the criteria "Good". The research hypothesis was analyzed using the MANOVA test, so that the results obtained were : namely , and namely then rejected and accepted. Thus, it can be concluded that there is an influence of the integrated causal learning model of local wisdom on the mastery of environmental concepts and literacy in the global warming material of class X students.